PANDANGAN GEREJA KATOLIK TENTANG KOMUNIKASI SOSIAL BERDASARKAN KHK 822 DAN RELEVANSINYA BAGI LITERASI DIGITAL UNTUK KAUM MUDA - Patrisius Epin Du; Gaspar Triono Jeraman; Yohanes Endi (Lembaga Penelitian STKIP Widya Yuwana, 2022)
The development of digital technology has both positive and negative impacts on the lives of young people. This issue shows that the negative impacts of technological developments are manipulation, increasing online violence, loss of a sense of community, lack of concern for others, and wanting to be noticed. This encourages the Church to develop digital literacy for young people. This study uses a literature study to explore the themes surrounding the Catholic Church's view on Social Communication based on Canon 822 and the importance of digital literacy for young people. The findings of this paper are that the Church is encouraged to be a model or role model for young people. The Church is called to foster dialogue with young people, and to develop creative and innovative pastoralists in the use of digital media.